Matching Livestock Systems With Feed Resources - Preston, Thomas R. (Technical Centre for Agricultural and Rural Cooperation, 1986)
If one compares the results obtained from programmes designed to improve crop and animal production in Third World countries, it becomes obvious that crop improvement has been more successful. Why is this so ~ One of the reasons is that most of the...